Material world and social recognition: Nursing care in Spain (1855-1955) - Arredondo-González, Claudia Patricia; Cuesta-Benjumea, Carmen; Ávila –Olivares, José Antonio (Investigación y Educación en Enfermería, 2015)
Objective. This study sought to recognize the active and symbolic role played by the objects from the material world for nursing care in Spain between 1855 and 1955. Methodology. This was a historical study using grounded theory procedures. The information sources were eight handbooks for the training of caring professionals published in Spain, during the period of interest. The information was gathered from March 2012 to June 2013. During this period, the sources were fully revised and index cards with bibliographic information, description of instruments, and analysis were elaborated; methodological and analytic memoranda were written. Forty-five procedures and 360 material objects were registered. Results. The categories “principal and secondary objects” and “guarded objects” reveal the influence exerted by the objects from the material world for care. Conclusion. In Spain, between 1855 and 1955, nursing care was carried out within a scenario comprised of objects with secondary status and situated within the periphery of care, as well as by guarded objects that professionals could not use. This material world influenced the social recognition of professional caregivers at the time and the visibility of their work. How to cite this article: Arredondo-González CP, De la Cuesta-Benjumea C, Ávila –Olivares JA. Material world and social recognition: nursing care in Spain (1855-1955). Invest Educ Enferm. 2015; 33(1):